Flexible mindsets in schools channelling brain power for critical thinking, complex problem-solving and creativity - Dunstan, Julie (Psychologist); Cole, Susannah (Routledge, Taylor & Francis Group, 2022)
"Flexible Mindsets in Schools abandons painstaking evolution in favour of a bold, transformative revolution. It blends research and easily implementable practice to drive solutions that give learners and educators the freedom to become self-directed: to unleash questioning, problem-solving and creativity. This key text explores how to blend existing and new practices and unlock the potential of student agency as the pathway towards resilience and adaptation. The Flexible Mindsets Modelfuses three components that rely on each other to drive self-directed learning: metacognition, "I CAN" mindset messages and executive function processes. This book presents a roadmap for how to create an environment and culture where learners are aware of what works when, feel safe to take learning-related risks, believe that they are capable and have the tools they need to learn. Flexible Mindsets in Schools will give educators hope that there is a way to revolutionize education to meet the needs of students during these uncertain times by taking small, manageable steps"--